2007
DOI: 10.1016/j.breast.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Interval breast cancers in screening: The effect of mammography review method on classification

Abstract: Surveillance of interval cancers (IC) lacks standardisation of review methodologies. We investigated the extent to which 'informed' or 'blinded' review may affect IC classification. This is a retrospective study of 100 validated screening mammograms (20 IC, 80 negative screens) independently reviewed by six radiologists. Three sequenced review methods with increasing information were used: (1) blinded (no IC information, case mix), (2) partially informed, and (3) fully informed. IC 'screening error' (SE) repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 11 publications
2
37
0
5
Order By: Relevance
“…In addition, radiological classification of interval cancers is not easy to perform, and well-established protocols are lacking. Consequently, comparison of the results on interval cancers is difficult, given that many studies follow different strategies of interval classification [37]. We performed two mammographic reviews with both blinded and unblinded components, as recommended by the European Guidelines [4].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiological classification of interval cancers is not easy to perform, and well-established protocols are lacking. Consequently, comparison of the results on interval cancers is difficult, given that many studies follow different strategies of interval classification [37]. We performed two mammographic reviews with both blinded and unblinded components, as recommended by the European Guidelines [4].…”
Section: Discussionmentioning
confidence: 99%
“…IC cases (N=100) and controls (N=200) did not differ as [8,9]. Il tasso di incidenza proporzionale e di ES così ottenuto sono stati confrontati con gli standard internazionali e con i risultati di altri programmi di screening nazionali e esteri.…”
Section: Resultsunclassified
“…IC review was largely within recommended values (SE rate=15% vs. ≤20% recommended) and confirmed a good performance of the Verona screening programme in terms of sensitivity. Blind review of IC is the most correct methodology to assess potential reading errors [8,9], as it tends to reproduce the current screening scenario, where radiologists are not aware of which cases will develop IC, among a large majority of true negative cases. Blind review, recommended by the Italian Study Group for Mammography Screening (GISMa) [1], has been recently suggested as a standard procedure by the Italian Ministry of Health [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of the review strategy used in this work is the blinded classification and the case-mix (cancers and controls) which are recommended methods for radiological reviews to help reduce the bias in the classification of mammograms [7,11] and to approximate the scenario of screening practice [1,2]. Nonetheless, in a research context, reviewers might be expected to achieve higher sensitivity and lower specificity by adopting a lower threshold for suspicion, as suggested by the recall rates (see Table 2) which were higher than in routine practice, but comparable to other studies using radiological reviews [11][12][13]. The applied comparison of reviews of T2+ and ICs is reliable (performed by the same radiologist panel in the same setting using a standardised set of negative controls) and was performed to interrogate the extent to which preceding mammograms for these cancers would be classified as screening errors.…”
Section: Discussionmentioning
confidence: 99%